Applicability of the modified ACOG/SGO referral criteria for adnexal mass within a limited‐resource setting. Issue 1 (3rd November 2016) - Battarbee, Ashley; Strohl, Anna; Zimmerman, Lindsay; Patel, Ashlesha; Burtch, Radha
Abstract: Objective: To evaluate the performance of the modified American Congress of Obstetricians and Gynecologists (ACOG)/Society of Gynecologic Oncology (SGO) referral guidelines in a high‐risk limited‐resource setting. Methods: In a retrospective study, data were assessed for all women who underwent surgery for an adnexal mass at John H. Stroger Jr Hospital, Chicago, IL, USA, between July 2006 and July 2011. Sensitivity, specificity, and positive and negative predictive values were calculated both for actual practice referral patterns and for the modified ACOG/SGO guidelines. Results: Among 542 study women, 176 (32.5%) were diagnosed with ovarian malignancy. The ACOG/SGO guidelines showed 81.3% sensitivity and 71.9% specificity for the prediction of malignancy at time of surgery, with positive and negative predictive values of 58.1% and 88.9%, respectively. Actual practice patterns demonstrated lower sensitivity (68.2%; P <0.001) but higher specificity (84.2%; P <0.001). Conclusion: As compared with practice patterns, the modified ACOG/SGO guidelines lacked sufficient specificity for referral and might not be applicable in high‐risk, low‐resource settings. For this population, screening should be based on stratifying patients into low‐, intermediate‐, and high‐risk categories to allow limited resources to be focused on women at highest risk. Abstract : The modified American Congress of Obstetricians and Gynecologists/Society of Gynecologic Oncology referral guidelines for adnexal mass lack sufficient specificity in a high‐risk, limited‐resource setting.